(untitled) (Analysis in Theory and Applications, 2022)
In this paper, we consider the area function S_Q related to the Schrödinger operator L and its commutator S_Q,b, establish the boundedness of S_Q from H^p_ρ(w) to L^p(w) or WL^p(w), as well as the boundedness of S_Q,b from H^1_ρ(w) to WL^1(w).